DNA Barcoding of Commercial Fish Sold in Muar Fish Market, Johor - Othman, Nursyuhada; Abel, Jaevilynecrisse; Haris, Hidayah; Ilham-Norhakim, Mohd Lokman; Munian, Kaviarasu; Ramli, Farah Farhana; Sariyati, Nur Hartini; Najmuddin, Mohd Faudzir; Abdul-Latiff, Muhammad Abu Bakar (Journal of Sustainable Natural Resources, 2023)
Due to the high demand in the fisheries market, species identification is vital for commercial fish to avoid mislabeling and fraud in marketplaces. The increasingly threatening human activities like overfishing, blast fishing, poison fishing, and trawling have become the major threats to fish and caused an urgent need for documentation of both marine and freshwater fishes. Commercial fish products sometimes are sold by their parts, such as fins which further create confusion for identification purposes. Morphological identification also requires highly skilled ichthyologists to avoid misidentification. Thus, identification through DNA barcoding can be utilized as it holds the potential for accurate and rapid identification. Here we identified the commercial marine fish species sold in Muar Fish Market, Johor, using the Cytochrome Oxidase subunit I (COI) gene of mitochondrial DNA (mtDNA). A 700 base-pair sequence of the COI region was targeted by amplifying extracted DNA from 28 fin samples collected from the fish market. From 28 samples, we successfully sequenced 16 samples, and by using phylogenetic analysis, (Neighbor-Joining (NJ), Maximum Parsimony (MP) and Bayesian Inference (BI)) we successfully identified the samples belonging to nine families (Scombridae, Platycephalidae, Carangidae, Ariidae, Polynemidae, Coryphaenidae, Sphyraenidae, Muraenesocidae, Engraiulidae), 12 genera and 16 species. This study reports the first documentation of commercial fish sold in Muar through the DNA barcoding technique. This technique should be expanded further to identify any species with important conservation implications, such as endangered species, for improved management of fisheries in Malaysia.